2020
DOI: 10.1038/s41467-020-16395-2
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 and ISGylation is required for pancreatic cancer stem cell mitophagy and metabolic plasticity

Abstract: Pancreatic cancer stem cells (PaCSCs) drive pancreatic cancer tumorigenesis, chemoresistance and metastasis. While eliminating this subpopulation of cells would theoretically result in tumor eradication, PaCSCs are extremely plastic and can successfully adapt to targeted therapies. In this study, we demonstrate that PaCSCs increase expression of interferon-stimulated gene 15 (ISG15) and protein ISGylation, which are essential for maintaining their metabolic plasticity. CRISPR-mediated ISG15 genomic editing red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 56 publications
(93 reference statements)
4
78
0
Order By: Relevance
“…Cells were analyzed with a 4-laser Attune NxT acoustic cytometer (ThermoFisher Scientific, Waltham, MA, USA). Cells and digested tumors (as described in [ 22 ]) were resuspended in FLOW buffer (1X PBS; 3 mM EDTA ( v/v ); 3% FBS ( v/v )), and the following fluorescent-tagged antibodies were used to label cells for 30 min at 4 °C: mouse monoclonal antihuman CD133-APC (1:20, Cat no. 130-111-080, Miltenyi, Bergisch Gladbach, Germany) or mouse monoclonal antihuman C-X-C chemokine receptor type 4-phycoerythrin (CXCR4-PE; 1:20, Cat no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were analyzed with a 4-laser Attune NxT acoustic cytometer (ThermoFisher Scientific, Waltham, MA, USA). Cells and digested tumors (as described in [ 22 ]) were resuspended in FLOW buffer (1X PBS; 3 mM EDTA ( v/v ); 3% FBS ( v/v )), and the following fluorescent-tagged antibodies were used to label cells for 30 min at 4 °C: mouse monoclonal antihuman CD133-APC (1:20, Cat no. 130-111-080, Miltenyi, Bergisch Gladbach, Germany) or mouse monoclonal antihuman C-X-C chemokine receptor type 4-phycoerythrin (CXCR4-PE; 1:20, Cat no.…”
Section: Methodsmentioning
confidence: 99%
“…While these alarming statistics can be attributed to the fact that PDAC is typically diagnosed at advanced stages, due to a lack of both symptoms and sensitive/specific markers for early detection [ 16 ], the existence of pancreatic CSCs (PaCSCs) [ 17 , 18 ] likely also plays an important role in the poor prognosis of this disease and contributes to the inherent aggressiveness as well as the chemotherapy- and radiotherapy-resistant nature of this tumor. Over the past 13 years, we have come to realize that PaCSCs are not merely a distinct subpopulation of tumor cells, but these cells are biologically different from their non-CSC counterparts on the epigenetic [ 19 ], transcriptional [ 20 ], metabolic [ 21 ], and protein levels [ 22 , 23 , 24 , 25 ], and that these differences drive their tumorigenic, chemo-resistant, and metastatic potential, but, at the same time, may represent weaknesses that can be exploited therapeutically.…”
Section: Introductionmentioning
confidence: 99%
“…Since CSCs are particularly sensitive to inhibition of mitochondrial function and oxidative damage [9,11], these treatment effects of mDivi-1 could, at least in part, explain its marked toxicity in CSCs. Notably, mDivi-1 treatment also increased the expression of LC3B ( Figure S3D), which suggests the activation of autophagy as a counteractive mechanism to avoid the excessive accumulation of defective mitochondria; however, as we have previously shown [12], activation of autophagy does not necessarily ensure mitophagy, especially not when fission is inhibited.…”
Section: Mdivi-1 Treatment Disrupts Mitochondrial Functionmentioning
confidence: 65%
“…We have recently demonstrated that mitochondrial biogenesis driven by PGC1-, and recycling of dysfunctional mitochondria through ISGylation-mediated mitophagy are essential processes for pancreatic CSCs [9,12]. In between these initial and final steps in the lifecycle of mitochondria, fusion and fission represent the main events involved in mitochondrial dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…13 Some previous studies showed that the critical role of CSCs in initiation and development of lung cancer, liver cancer, breast cancer, head and neck squamous cell carcinomas, pancreatic cancer and glioblastoma. [14][15][16][17][18][19] Lung CSCs are considered as the cancer initiating and maintaining cells of lung cancer. 15 Lin et al reported that lung CSCs are responsible for lung cancer initiation and local or metastatic recurrence, the mitochondrial deoxyguanosine kinase is required for CSCs stemness in lung adenocarcinoma.…”
Section: Cancer Stem Cells Play a Key Role In Tumorigenesis And Develmentioning
confidence: 99%